2021
DOI: 10.3389/fimmu.2021.796493
|View full text |Cite
|
Sign up to set email alerts
|

The HSP Immune Network in Cancer

Abstract: Heat shock proteins are molecular chaperones which support tumor development by regulating various cellular processes including unfolded protein response, mitochondrial bioenergetics, apoptosis, autophagy, necroptosis, lipid metabolism, angiogenesis, cancer cell stemness, epithelial-mesenchymal transition and tumor immunity. Apart from their intracellular activities, HSPs have also distinct extracellular functions. However, the role that HSP chaperones play in the regulation of immune responses inside and outs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 147 publications
(198 reference statements)
0
17
0
Order By: Relevance
“…GRP94 functions are not restricted to UPR, as GRP94 showed to be a critical immune chaperone [reviewed in (37)] (159). It has been shown that GRP94 is a chaperone for integrins and leucinerich repeats domain 32 (LRRC32), also known as GARP, a docking protein for the membrane expression of transforming growth factor -b (TGF-b) (159,160).…”
Section: Er Hsp90 and Hsp70 In Cancer Grp94/hsp90b1/gp96/erp99/ Endoplasminmentioning
confidence: 99%
See 1 more Smart Citation
“…GRP94 functions are not restricted to UPR, as GRP94 showed to be a critical immune chaperone [reviewed in (37)] (159). It has been shown that GRP94 is a chaperone for integrins and leucinerich repeats domain 32 (LRRC32), also known as GARP, a docking protein for the membrane expression of transforming growth factor -b (TGF-b) (159,160).…”
Section: Er Hsp90 and Hsp70 In Cancer Grp94/hsp90b1/gp96/erp99/ Endoplasminmentioning
confidence: 99%
“…Furthermore, HSP70 and HSP90 family members and co-chaperones have been shown to be released by immune cells in extracellular vesicles (8,(32)(33)(34)(35)(36). It is also worth mentioning that extracellular HSP70 and HSP90 homologs modulate various components of the immune system [reviewed in (37)]. Currently, various studies are aimed at exploiting extracellular HSPs as a diagnostic tool and as therapeutic targets (8,(38)(39)(40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%
“…During this process, the intracellular HSPs (iHSPs) transfer through the cellular membrane and into the ECM [ 18 ]. The secretion of HSPs on the membrane (mHSPs), or release of them into the ECM (eHSPs), appears to be associated with lysosomal endosomes or via the release of exosomes containing HSPs [ 19 ]. The iHSP may be translocated to the cellular membrane via the same transport pathway of secretory lysosomes during this process.…”
Section: Heat Shock Proteinsmentioning
confidence: 99%
“…Regarding HSP27, as far as we know, no studies have investigated the possibility to target this small HSP in the treatment of PEL. Of note is that among the numerous proteins stabilized by HSPs, there are oncogenes such as mutp53 [ 13 ] and c-MYC [ 14 ], epidermal growth factor receptor (EGFR) and the molecules involved in its mediated signaling cascade [ 15 ], and proteins involved in processes such as cell cycle progression and angiogenesis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%